Chitosan-Based Scaffolds for Facilitated Endogenous Bone Re-Generation - Yao Zhao; Sinuo Zhao; Zhengxin Ma; Chunmei Ding; Jingdi Chen; Jianshu Li (MDPI AG, 2022)
Facilitated endogenous tissue engineering, as a facile and effective strategy, is emerging for use in bone tissue regeneration. However, the development of bioactive scaffolds with excellent osteo-inductivity to recruit endogenous stem cells homing and differentiation towards lesion areas remains an urgent problem. Chitosan (CS), with versatile qualities including good biocompatibility, biodegradability, and tunable physicochemical and biological properties is undergoing vigorously development in the field of bone repair. Based on this, the review focus on recent advances in chitosan-based scaffolds for facilitated endogenous bone regeneration. Initially, we introduced and compared the facilitated endogenous tissue engineering with traditional tissue engineering. Subsequently, the various CS-based bone repair scaffolds and their fabrication methods were briefly explored. Furthermore, the functional design of CS-based scaffolds in bone endogenous regeneration including biomolecular loading, inorganic nanomaterials hybridization, and physical stimulation was highlighted and discussed. Finally, the major challenges and further research directions of CS-based scaffolds were also elaborated. We hope that this review will provide valuable reference for further bone repair research in the future.